2021
DOI: 10.1177/10711007211051642
|View full text |Cite
|
Sign up to set email alerts
|

Distal Metatarsal Articular Angle in Hallux Valgus Deformity. Fact or Fiction? A 3-Dimensional Weightbearing CT Assessment

Abstract: Background The Distal Metatarsal Articular Angle (DMAA) was previously described as an increase in valgus deformity of the distal articular surface of the first metatarsal (M1) in hallux valgus (HV). Several studies have reported poor reliability of this measurement. Some authors have even called into question its existence and consider it to be the consequence of M1 pronation resulting in projection of the round-shaped lateral edge of M1 head. Our study aimed to compare the DMAA in HV and control populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…We previously reported an increase in M1 head pronation relative to the ground in HV patients. 7 In the present study, individual measurements of the rotation of the bones composing the medial column revealed an increase in pronation of M1 intrinsic torsion and first tarsometatarsal joint position in HV compared with controls, confirming our hypothesis. This pronation was paradoxically and partially counterbalanced by an increase in supination of the first naviculocuneiform joint.…”
Section: Discussion/conclusionsupporting
confidence: 89%
See 1 more Smart Citation
“…We previously reported an increase in M1 head pronation relative to the ground in HV patients. 7 In the present study, individual measurements of the rotation of the bones composing the medial column revealed an increase in pronation of M1 intrinsic torsion and first tarsometatarsal joint position in HV compared with controls, confirming our hypothesis. This pronation was paradoxically and partially counterbalanced by an increase in supination of the first naviculocuneiform joint.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…This was a retrospective case-control study, approved by the institutional review board (IRB 201904825), that used the same cohort of our previous article, including 36 HV and 20 control feet (matched for gender age and body mass index). 7 We previously performed and published a cadaveric study to assess the relevance and the accuracy of several weightbearing CT coronal plane rotation measurements throughout the medial column of the foot. 4 In this study, coronal rotational profiles of the navicular, medial cuneiform, M1 at base and midshaft levels, as well as the metatarsal pronation angle and α angles were established.…”
Section: Methodsmentioning
confidence: 99%
“…There is growing interest in the use of minimally invasive surgical techniques (MIS) for the treatment of hallux valgus (HV), with an increasing number of published studies including clinical series, radiologic validations, cadaveric studies, comparative studies, and technical reports on MIS techniques. 1,4,[8][9][10][15][16][17][18][19][20][21]23,[26][27][28][29][30][31][32][33][34][35][36][39][40][41][42][43]45,55,[59][60][61][62][63][64]66,70 Five recent systematic reviews concluded that MIS is a safe and reliable technique for hallux valgus correction. 6,11,28,44,65 Among the procedures to treat HV, the distal chevron metatarsal osteotomy was first described in 1962 and remains a widely accepted technique.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]10 It has been shown that there are significantly higher levels of first metatarsal pronation in feet with hallux valgus deformity as compared to controls. 3 Further, it has been shown that correction of pronation in hallux valgus results in significantly improved PROMIS physical function scales and reduced recurrence rates compared to no correction of rotation in the coronal plane. 1 Therefore, addressing first metatarsal pronation is an area of topical interest as it may improve outcomes in operative correction of hallux valgus.…”
Section: Introductionmentioning
confidence: 99%